Systematics of north African Agama (Reptilia: Agamidae): a new species from the central Saharan mountains - Geniez, Philippe; Padial, José M.; Crochet, Pierre-André (Zootaxa, 2011)
We studied the taxonomic status of the north African Agama species A. impalearis, A. castroviejoi, and A. boueti. The study of recently collected specimens and museum material, as well as phylogenetic analyses of a short 16S ribosomal RNA gene fragment, revealed the presence of an undescribed species in Adrar des Ifoghas (Mali), Aïr Mountains (Niger), Ahaggar Mountains (Algeria) and Tassili n’Ajjer (Algeria, Lybia), previously mistaken either as A. impalearis or A. agama. The new species, Agama tassiliensis n. sp., clearly belongs to the impalearis – boueti – spinosa species group but differs from these species, among other characters, by its red, reddish-orange or orange vertebral stripe in males, long and angular head, long limbs and toes (with 4 th toe usually slightly longer than 3 rd toe), long but low nuchal crest made of 10 to 15 spines (rarely 8–9 spines) and large number of supralabials (10–16, usually around 12). Interspecific uncorrected p- distances based on the 16S rDNA gene fragment are high, ranging from 3.9% between A. boueti and A. impalearis to 7.9% between A. spinosa and A. impalearis. The new species is sympatric with A. boueti at least in the Aïr Mountains and exhibits average mtDNA divergences of 6.2%, 7.4%, and 7.6% with A. spinosa, A. impalearis, and A. boueti, respectively. Agama boueti is paraphyletic relative to A. castroviejoi in the mtDNA tree, and mtDNA genetic divergences between populations of both species are lower than 1.0%, suggesting that A. castroviejoi is better treated as a junior synonym of A. boueti pending more detailed analyses. Scattered mountain ranges in the Sahara seem to have promoted lineage divergence and ultimately speciation in this group. Further work should be done to study species taxonomy and evolution in those areas.